From Legalized to Legal English: The Challenge of ESP - Hall, Charles (Armenian Folia Anglistika, 2005)
The English teaching of the students majoring in law will be more effective if it begins with legal texts not designed for specialists. This would enable the students to overcome the language-related difficulties in original legal texts and to make appropriate analysis.